AS RELAÇÕES ENTRE SUPORTE SOCIAL E BALANÇO EMOCIONAL - Freitas, Ion de (2009)
The goal of this study was to describe the dimension levels of social support (emotional and practical) and of emotional balance, to analyze its correlations and to investigate its relations with socio-demographic variables of a group of people who participate of a program of emotional and informational support in a charity institution of São Paulo. The researched sample, chosen randomly, consisted of 95 males and females with average age of 47, 99 years (SD=12,11). The gathering data instrument was an auto fill questionnaire composed by two measures which checked the variables of the study (perception, social support, positive and negative affects), besides the socio-demographic data. Descriptive statistic analyzes were used, differences between averages were tested, and correlation rates between variables were calculated as well. The results have shown that there are no significant differences in the perception of social support (emotional and practical) and the socio-demographic variables, sex, work, study, volunteering, time at the institution, level of education and marital status. The youngest, less than 30 years old, revealed more perception of social support (emotional and practical). They also revealed that there is no significant difference of the emotional balance towards the socio-demographic variable, except for the volunteer work which echoed expressive and positively over the emotional balance. The analyses of the relations between social support (emotional and practical) and age revealed the existence of a significant correlation, low and negative, that is, with an increase in age there s a tendency to lightly describe the perception of social support. The description of the levels of social support revealed that the perceptions of emotional and practical support (tangible and appraisal support) are significantly different, though the difference between the averages is small, prevailing the perception of higher emotional support. The description of the emotional balance scores showed that around three quarters of the interviewed have registered positive emotional balance and around one fourth have registered negative emotional balance. Significant correlation between emotional balance and age were not identified. The analyses of the relations between emotional support, practical support and emotional balance reveled significant and positive correlations, that is, with an increase in perception of the social support (emotional and practical) there is a tendency to increase the emotional balance. The results of this study might contribute to the comprehension of the psychological state of the investigated individuals, as well as, raise, to the managers of institutions, reflections on the improvement of assistential program services.(AU)